The Main Character’s Loss,Emptiness and Object of Desire in Markus Zusak’s The Book Thief - Rizka Merdifa (English Department, Faculty of Humanities, Andalas University, 2018)
This thesis shows the result of the analysis toward Markus Zusak’s novel The Book Thief by using psychological approach. The focus of this research is Liesel Meminger’s personality as the main character which is assumed suffers from trauma and anxiety after losing the important people in her life. This research uses psychoanalytical theory by Lacan about human’s real, symbolic and imaginary; and also theory of anxiety by Freud. This research concludes that Liesel indeed suffers from trauma and anxiety which is shown by some symptoms found in her that caused by the loss of her parents and brother at young age. This loss has created a situation as if Liesel felt empty and she unconsciously longs to fulfill that emptiness. A book she had stolen in her brother funeral gives significant contribution toward Liesel’s desire in symbolic order to fulfill her lack and emptiness, but the book has also caused her to get trapped in her imaginary order until in the end, Liesel could finally find self-realization and heal from her trauma.